2019
DOI: 10.3390/min9020124
|View full text |Cite
|
Sign up to set email alerts
|

Selective Separation of Hematite by a Synthesized Depressant in Various Scales of Anionic Reverse Flotation

Abstract: Demand for high-quality iron concentrate is significantly increasing around the world. Thus, the development of the techniques for a selective separation and rejection of typical associated minerals in the iron oxide ores, such as phosphorous minerals (mainly apatite group), is a high priority. Reverse anionic flotation by using sodium silicate (SS) as an iron oxide depressant is one of the techniques for iron ore processing. This investigation is going to present a synthesized reagent “sodium co-silicate (SCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Since CaO exists in the chemical composition of SCS, minor activation of quartz's surface is expected. [16] Nevertheless, it can be concluded that the depressant adsorptions on the quartz's surface have no significant effect on its flotation behavior. Although in the RAF, due to the quartz's negative surface charge, it is not expected that its particles floated with the anionic collector, micro-flotation tests indicate around 21% of quartz particles are floated.…”
Section: Quartzmentioning
confidence: 99%
See 3 more Smart Citations
“…Since CaO exists in the chemical composition of SCS, minor activation of quartz's surface is expected. [16] Nevertheless, it can be concluded that the depressant adsorptions on the quartz's surface have no significant effect on its flotation behavior. Although in the RAF, due to the quartz's negative surface charge, it is not expected that its particles floated with the anionic collector, micro-flotation tests indicate around 21% of quartz particles are floated.…”
Section: Quartzmentioning
confidence: 99%
“…The SCS is a modified SS, but unlike the SS gel, it is in the form of solid white powder. [16] NaOH (analytical grade) solution was used to modify the pH value (around 9.5) of the flotation pulp and also gelatinization of starch (at a ratio of 5:1). For the flotation tests in the presence of SCS, no pH modifier was added since SCS can play both pH modifier and depressant roles.…”
Section: Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mineral flotation separation, as a physicochemical process, is a well-known technique for the purification of target minerals which become finely liberated (mainly +25-100 micron) [1,2]. Currently, froth flotation is globally considered for processing various finely disseminated minerals (sulphides [3][4][5][6], oxides [7][8][9][10][11][12], silicates [7,8,10,12], phosphates [7,13,14], etc). In direct flotation, target minerals are floated, whereas in reverse flotation, valuable minerals are sunk, and gangue minerals are rejected in the froth phase [1,2].…”
Section: Introductionmentioning
confidence: 99%